Enhancement of the photocatalytic performance of Ru-doped TiO2 nanoparticles - Wetchakun K. (2014)
Pure TiO2 nanoparticles were synthesized by the modified sol-gel method using titanium tetraisopropoxide (TTIP) precursor dissolved in absolute ethanol. A pouch type cellophane membrane was employed as barrier between the precursor solution and the mixture of absolute ethanol (1:1 v/v) and distilled water with 0.5-1.0 % concentrated of ammonia in order to fix the reaction activity inside the pouch and control diffusion rate of hydrolysis and condensation reaction. The doping of TiO2 nanoparticles with 0.1, 0.2, 0.5, 1.0 and 2.0 at.% Ru was performed by the impregnation method using ruthenium acetyl acetonate in toluene as dopant. The properties of the all samples were characterized by X-ray diffraction (XRD), Brunauer, Emmett and Teller (BET)-specific surface area, Scanning electron microscopy-Energy dispersive spectroscopy (SEM-EDS) and transmission electron microscopy (TEM). The crystalline size of pure TiO2 and Ru-doped TiO2 nanopaticles were found to be in the range of 10-20 nm. The photocatalytic mineralization of formic acid, oxalic acid, sucrose and glucose was investigated using Degussa P25, pure TiO2 and Ru-doped TiO2 nanoparticles as photocatalysts in aqueous solutions under UVA irradiation. The rate of 50% mineralization of formic acid by 0.1 at.% Ru-doped TiO2 was 1.53 times and 1.34 times higher than that of pure TiO2 and Degussa P25, respectively showing the enhancement of the photocatalytic performance of TiO2 by doping with an optimum amount of ruthenium. © 2008 Trans Tech Publications, Switzerland.